Cycling cities: the Arnhem and Nijmegen experience. - Berkers, Eric; Oldenziel, Ruth (My University, 2017)
The Dutch cities of Arnhem and Nijmegen both have a rich history of every aspect of cycling: utilitarian, leisure, and sport. Separated by two rivers for so long, today they are drawn closer through the cycle highway RijnWaalpad, aptly named after the rivers. The fast cycle route symbolizes their newfound joint efforts to encourage cycling as a healthy, efficient, and sustainable means of transport for this urban region. The book traces the fascinating cycling histories of Arnhem and Nijmegen - from cycling tourists in 1900 scaling the region's charming yet hilly landscape to urban commuters navigating the car-governed urban planning of the 1950s and 1960s and from cycling activists of the 1970s and the local and regional policymakers committed to cycling over the last two decades.
Keywords: Stadtverkehr; Fahrradverkehr; Radverkehr; Verkehrsplanung; Verkehrsentwicklung; Mobilität; Verkehrspolitik; Verkehrsentwicklung; Verkehrsgeschichte